Preliminary Study on the Structure of the Peutswamp Forest in Padang Island, Rdpu Province - Haryanto . (Department of Forest Resources Conservation and Ecotourism - IPB University, 1989)
Pulau Padang forest vegetation is a typical peatswamp forest on ombrogenous peat, that is the most common peat in eastern coaat of Sumktcan. The peat is characterized by very acid d r a m watu and poorness in nutrients (oligotrophic).The surface of the peatswamp is abnest bsy sdth e raech of flood-wata and tides, except for a thin layer of mangrove forest arround the coast. There are no nutrients entering the system from the mineral soil below the peat, and the only nutrients input comes from the nutrient-poor rain. Because of this conditions, there is a decrease toward the centre of the peat areas in the ammounts of mineral nutrients in the soil. This trend of infertility seems to be reflected by the: (1) decreasing canopy height; (2) decreasing total biomass per unit area; (3) increasing leaf thickness as an adaptation to poor soil; (4) decreasing species diversity and (5) abundance of poor nutrients indicator species, especially Nepenthes spp. This paper describe the vegetation structure and the composition of peatswamp forest in pulau Padang, Riau, including mixed peatswamp forest, Bintangor (Calophyllum spp.) forest and shrub vegetation. Intersting is the dominance of Calophyllum spp. and some other members of the Family Clusiaceae (Guttiferae) which is rarely reported as dominant species in peatswamp forest formation, however, Anderson (1976) has ever reported the dominance of Calophyllum retusum in the peatswamp forest in Sebangau, Kalimantan Tengah.